THE IMPORTANCE OF TEACHING COMBINATORIAL CONTENT PROBLEMS IN PRIMARY GRADES USING INNOVATIVE METHODS - Toshboyeva Saidakhon (Bright Mind Publishing, 2025)
The article analyzes the importance of innovative methods in teaching combinatorial problems to primary school students. The theory of combinatorics, its history of development and practical significance are presented. Effective methods for explaining combinatorial problems based on modern interactive methods, digital technologies and the STEAM approach are also presented. The importance of using games and visual methods to increase students' interest, develop logical thinking skills and increase the effectiveness of the lesson is highlighted. The article presents interactive platforms, group exercises and game methods that ensure the active participation of students, and shows their positive impact on the educational process.
Keywords: Primary school, combinatorics, interactive methods, digital technologies, STEAM, game-based education, logical thinking, mathematics, didactic games, educational innovations.